Cognitive mechanisms of connotative semes formation in adjectives - A V Medvedeva (Russian journal of linguistics: Vestnik RUDN, 2009)
The article is devoted to the study of metaphor as one of a cognitive mechanisms of figurative meaning formation in adjectives. Semantic system of a language is regarded as the reflection of cognitive processes of human mind.